European Chemistry Partnering: Chemistry Makes the World Go Around!. Issue 11 (20th August 2018) - Bengs, Holger
Abstract: Chemistry continually reinvents itself. Chemical production everywhere is influenced by new disciplines, from industrial biotechnology to the Internet of Things; and every traditional as well as new area of expertise has its specialists. Solutions for the big challenges, however, can only be found in interdisciplinary exchange and in complementary cooperation. Scientific congresses and fairs for existing business follow well established formats. To accelerate finding innovations, an industry speed dating format now exists for the chemical industry. Young start‐ups play a crucial role here. Abstract : New technologies like industrial biotechnology or internet of things are changing the processes in chemical value creation: Interdisciplinary exchange is gaining in importance. With the European Chemistry Partnering, an international chemistry community is growing that wants to derive more innovation from what already exists.